The testament of Sheikh Abdullah ; with a monograph by Y. D. Gundevia - Abdullah, Mohammad, Sheikh, 1905-1982 (Palit & Palit : sole distributors, Abhinav Publications, New Delhi, 1974)
On the political views of the Kashmiri leader Sheikh Mohammad Abdullah, b. 1905.